FGF21 Serum Levels in the Early Second Trimester Are Positively Correlated With the Risk of Subsequent Gestational Diabetes Mellitus: A Propensity-Matched Nested Case-Control Study - Wang, Zhiheng; Yuan, Min; Xu, Chengjie; Zhang, Yang; Ying, Chunmei; Xiao, Xirong (Frontiers in Endocrinology, 2021)
Background: As an important endocrine hormone regulating glucose metabolism, fibroblast growth factor 21 (FGF21) is increased in individuals with gestational diabetes mellitus (GDM) after 24 gestational weeks. However, it is unknown whether the increase in FGF21 precedes the diagnosis of GDM. Methods: In this nested case-control study, 133 pregnant women with GDM and 133 pregnant women with normal glucose tolerance (NGT) were identified through propensity score matching, and serum FGF21 levels were measured at 14-21 gestational weeks, before GDM is routinely identified. The differences in FGF21 levels were compared. The association between FGF21 and the occurrence of GDM was evaluated using logistic regression models with adjustment for confounders. Results: The serum FGF21 levels of the GDM group at 14-21 gestational weeks were significantly higher than those of the NGT group overall (P<0.001), with similar results observed between the corresponding BMI subgroups (P<0.05). The 2nd (OR 1.224, 95% CI 0.603-2.485), 3rd (OR 2.478, 1.229-5.000), and 4th (OR 3.419, 95% CI 1.626-7.188) FGF21 quartiles were associated with greater odds of GDM occurrence than the 1st quartile after multivariable adjustments. Conclusions: The serum FGF21 levels in GDM groups increased in the early second trimester, regardless of whether participants were stratified according to BMI. After adjusting for confounding factors, the FGF21 levels in the highest quartile was associated with more than three times higher probability of the diagnosis of GDM in the pregnancy as compared to levels in the first quartile.